69 - CHARACTERISTICS OF HEALTH AND CARE OF PATIENTS WITH VENOUS ULCERS (Fiep Bulletin - online, 2011)
A cross-sectional descriptive quantitative approach carried out at Universitary Hospital Onofre Lopes (UHOL) aimed at characterizing the factors of health and care of patients with venous ulcers. Was approved by the Research Ethics Committee (279/09). Data collection took place from May to July 2009. The sample consisted of 50 patients. The data were organized in Excel and analyzed in SPSS 15.0. Patients were predominantly female (76.0%), with ages less than 59 years (74.0%), with low education predominated (68.0%), married (62.0%), Catholics (68, 0%), with more than three children (38.0%), with wage income of up to 2 minimum wages (72.0%), with inadequate sleep (50.0%) and IVC (100.0%). The results show that patients with longer lesions are most frequently seen by USF that the specialized hospital having more insomnia, more injuries and make more use of topical healing.
Keywords: venous ulcers; nursing